1998
DOI: 10.1063/1.477696
|View full text |Cite
|
Sign up to set email alerts
|

Core hole effect in NEXAFS spectroscopy of polycyclic aromatic hydrocarbons: Benzene, chrysene, perylene, and coronene

Abstract: Carbon K-edge NEXAFS spectra of chrysene, perylene, and coronene were measured using synchrotron radiation, and the results were analyzed by ab initio molecular orbital (MO) calculations. The spectra do not agree well with the calculated density of unoccupied states (DOUS), indicating significant core-hole effect leading to deviation of the NEXAFS spectra from the DOUS. On the other hand, the observed spectra were well simulated by theoretical calculations taking this effect into account by the improved virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
81
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 28 publications
16
81
0
Order By: Relevance
“…This substantiates the importance of core hole screening which influences the NEXAFS spectra differently depending on the location and chemical environment of the excitation center. It is consistent with earlier work by by Oji et al [18] and may callenge the validity of a constant energetic shift used in the static exchange approach [16,26].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This substantiates the importance of core hole screening which influences the NEXAFS spectra differently depending on the location and chemical environment of the excitation center. It is consistent with earlier work by by Oji et al [18] and may callenge the validity of a constant energetic shift used in the static exchange approach [16,26].…”
Section: Resultssupporting
confidence: 80%
“…It has been demonstrated that in many cases obtaining molecular NEXAFS signatures based on total densities of unoccupied states (DOUS) only is not fully conclusive [18]. The reason for this is the missing consideration of initial state effects which are due to differences in the C1s binding energies of differently coordinated carbon atoms within the molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] From the experimental point of view, the spectroscopic characterization of the molecular orbitals of the free PTCDI molecule, as well as of perylene, is largely outdated or limited. [15][16][17][18] In this context, the knowledge of the molecular orbital symmetry and energy, as measured in NEXAFS, is fundamental to understand the key parameters that govern the performances of an archetypal device, such as the orientation of the molecules on the surfaces 19 and the mechanism of charge transfer to the substrate. 20 In their extended review, Zahn and coworkers reported a comparative study of the electronic and vibrational properties of PTCDA and dimethyl-PTCDI, 2 however their analysis of NEXAFS spectra was limited to the comparison with previous calculations for naphthalene-tetracarboxylic dianhydride (NTCDA), 21 thus a clearcut disentanglement between initial and final state effects in the PTCDI NEXAFS is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…In the π* region, we observe five peaks, denoted as A, B, C, D and E. The most intense peaks at 284.9 and 285.3 eV are due to de C1s transitions to the LUMO π* states [20][21][22][23] of non-equivalent C sites in the molecules. 24,25 There is a large dichroism between the s-and p-polarised signals, even though the s-polarised signal does not vanish. The π* region is less intense for s-polarised light and the σ* region is less intense for p-polarises light.…”
Section: Resultsmentioning
confidence: 99%